Analisis dan Tren Penggunaan Accounting Choice yang dilakukan Perusahaan di Indonesia Pasca Adopsi IFRS - Heny Kurniawati (Binus Business Review, 2013)
This study aims to analyze the accounting choice used by Indonesia’s public listed companies after IFRS convergence effectively applied in 2011 and 2012. Data used in this study were financial statements of Indonesia’s public listed companies in 2011 and 2012. The analysis focused on accounting choice in fixed assets (PSAK 16), intangible assets (PSAK 19), and investment property (PSAK 13). The study showed that public listed companies tend to choose historical cost to account for their fixed assets, intangible assets, and investment property. For fixed assets, it is only 2.5% changing their accounting policy to revaluation method. While for investment property, it is only 15% using revaluation method. All of public listed companies used historical cost method to record their non-goodwill intangible assets.